Daulat-i Āṣafiyah aur ḥukūmat-i Bart̤āniyah - Maudoodi, Syed Abul ʻAla, 1903-1979 (SAMP early 20th-century Indian books project ;, 1941)
History of Princely State of Hyderabad during Asaf Jahi dynasty.